PEMALI MARRIAGE DECONSTRUCTION IN THE COMMUNITY OF BUSUNGBIU, BULELENG, BALI - Rustiani, Komang Wahyu; Suarka, I Nyoman; Mudana, I Gede (E-Journal of Cultural Studies; Volume 12, Number 3, August 2019DO - 10.24843/cs.2019.v12.i03.p04, 2019)
Forwarding pemali marriage expressions essentially are constituted by the myth, so they are essential to be analyzed since a lot of societies’ misinterpretation in creating meaning. The problems analyzed in this research are the form of pemali marriage, the deconstruction process on pemali marriage, and the relationship between pemali marriage in Busungbiu societies and local life. This is a qualitative research which used cultural studies paradigm. The data collection method utilizes observation, interview, and reviewing documents. The data were analyzed eclectically by utilizing deconstruction theory, cultural materialism theory, social semiotic theory, and encoding decoding theory. The research result shows that the forms of pemali marriage are related to kinship, physical features, social stratification, and time. The process of deconstruction on pemali marriage is done through three steps, they are deconstruction on the structure and the language code; reinterpretation on the meaning of pemali marriage; and representation on pemali in the marriage ritual in order to rationalize those pemali . The deconstruction on the relation between pemali marriage and the position of the subject is found in three positions; they are hegemony dominant positions, negotiation positions, and opposition position. Keywords:  pemali marriage, misinterprets, deconstruction, representation